NiTiHf alloy for aviation bearing and preparation method of NiTiHf alloy

By adding Hf elements to the NiTi alloy and optimizing the thermal processing parameters, the problem of insufficient elastic modulus and hardness of NiTi alloy is solved, and the high performance and good thermal processing properties of NiTiHf alloy for aviation bearings are achieved.

CN119392135AInactive Publication Date: 2025-02-07SHENYANG UNIVERSITY OF TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411528204.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The elastic modulus and hardness of existing NiTi alloys for aviation bearings are low, making it difficult to meet the lightweight, high corrosion resistance and wear resistance requirements of high-temperature bearing materials for aircraft engines in the future.

Method used

By adding Hf elements to NiTi alloys, using methods such as heat compression test and nanoindentation test, the mechanical properties of the alloy are evaluated, and the thermal processing window of the alloy is determined based on the material dynamic model, thereby formulating suitable thermal processing process parameters.

Benefits of technology

The high elastic modulus and excellent comprehensive mechanical properties of NiTiHf alloy are achieved, which solves the problem of narrow window of the alloy thermal processing temperature and provides a new type of material suitable for aviation bearings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392135A_ABST
    Figure CN119392135A_ABST
Patent Text Reader

Abstract

The invention provides a NiTiHf alloy for an aircraft bearing and a preparation method of the NiTiHf alloy. The method comprises the following steps: smelting Ni, Ti and Hf raw materials according to stoichiometry to obtain an alloy ingot; performing a thermal compression test on the alloy ingot to obtain stress-strain data of the alloy ingot; obtaining an energy dissipation diagram according to the relationship between the energy dissipation factor eta and the temperature as well as the strain rate, and obtaining a rheological instability diagram according to the relationship between the material rheological instability parameter xi and the temperature as well as the strain rate; and according to the energy dissipation diagram and the rheological instability diagram phase, a hot working diagram of the alloy ingot is obtained through superposition, hot working technological parameters of the alloy ingot are determined, and the hot working technological parameters comprise the hot working temperature and the strain rate. According to the method, the hot working parameters of the NiTiHf alloy with the specific stoichiometric ratio can be simply and conveniently determined, and therefore the problem that hot working is difficult due to the fact that the Hf element is introduced into the NiTi alloy can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of alloy materials, and in particular, to a NiTiHf alloy for aviation bearings and a preparation method thereof. Background Art

[0002] Nearly equiatomic NiTi alloys are widely used in aerospace, biomedicine and other fields because they can undergo reversible thermoelastic transformation between austenite with B2 structure and martensite with B19' structure, and have superelasticity and shape memory effect. At present, the main NiTi alloy used as aviation bearing material is 60NiTi alloy, which has been successfully used in bearings in the water circulation system of the International Space Station, effectively solving the wear and corrosion problems of bearings. As far as the development of high-temperature bearing materials for future aviation engines is concerned, it is particularly important to achieve the unity of light weight, high corrosion resistance and wear resistance under the premise of increasing its operating temperature. Among them, the contradiction between lightweighting of materials and improving elastic modulus is one of the main problems currently. Specifically, the elastic modulus and hardness of 60NiTi alloy are relatively low, and there is still room for further improvement.

[0003] Therefore, the current NiTi alloys for aviation bearings and their preparation methods still need to be improved. Summary of the invention

[0004] The embodiments of the present disclosure provide a NiTiHf alloy for aviation bearings and a preparation method thereof to solve or alleviate one or more technical problems in the related art.

[0005] As mentioned above, in order to further improve the elastic modulus and other properties of binary NiTi alloys, a feasible improvement method is to add other alloying elements to the alloy. However, the addition of alloying elements often leads to a decrease in the ductility of NiTi alloys, making it more difficult to meet the complex processing and forming processes of bearings. Therefore, the poor hot processing and forming properties of NiTi ternary alloys are an obstacle to its use as a bearing material. If it is possible to use alloying methods on the basis of binary NiTi alloys to ensure that the alloy has a high elastic modulus, while giving the alloy excellent comprehensive mechanical properties and solving the problem of the narrow hot processing temperature window of this type of alloy, then this system alloy is expected to become one of the important alternative materials for the development of new bearings for future aviation engines.

[0006] This application evaluates the mechanical properties of NiTiHf alloy through room temperature compression and nanoindentation tests, and reveals the hot working window of the alloy based on the material dynamic model, thereby formulating the hot working process parameters of the difficult-to-deform NiTiHf alloy, and further obtains a hot working method for NiTiHf alloy for aviation bearings with high elastic modulus and hot workable deformation.

[0007] As the first aspect of the present application, the present application proposes a method for determining the hot working parameters of NiTiHf alloy for aviation bearings. The method comprises: using Ni, Ti and Hf raw materials, and melting the alloy ingot according to the stoichiometric melting of the NiTiHf alloy; performing a hot compression test on the alloy ingot to obtain stress-strain data of the alloy ingot, the stress-strain data including the energy dissipation factor η and the material rheological instability parameter ξ of the alloy ingot under different hot deformation parameters; obtaining an energy dissipation diagram according to the relationship between the energy dissipation factor η and the temperature and strain rate, and obtaining a rheological instability diagram according to the relationship between the material rheological instability parameter ξ and the temperature and strain rate; superimposing the energy dissipation diagram and the rheological instability diagram to obtain the hot working diagram of the alloy ingot, and determining the hot working process parameters of the alloy ingot, the hot working process parameters including the hot working temperature and the strain rate. The method can easily determine the hot working parameters of NiTiHf alloy with a specific stoichiometric ratio, thereby solving the problem of hot working difficulties caused by the introduction of Hf elements into NiTi alloys.

[0008] According to the embodiment of the present application, in the thermal compression test, the thermal deformation parameters include deformation temperature and strain rate, the deformation temperature is 800-1000°C, and the strain rate is 0.001-1s -1 .

[0009] According to an embodiment of the present application, the hot compression experiment includes: heating the alloy ingot to a predetermined deformation temperature at a rate of 10K / s and maintaining the temperature for 5 minutes, stopping compression when the true strain is 0.9, and then water cooling.

[0010] According to an embodiment of the present application, the hot compression experiment is performed under a vacuum state, and graphite lubrication is used to reduce the friction between the alloy ingot and the clamping end.

[0011] According to an embodiment of the present application, obtaining the energy dissipation factor η and the material rheological instability parameter ξ includes:

[0012] The stress-strain curve of the alloy ingot under multiple thermal deformation parameters is obtained, the strain rate sensitivity index m is obtained, and based on the strain rate sensitivity index m, the energy dissipation factor η and the material rheological instability parameter ξ are calculated.

[0013] According to an embodiment of the present application, the strain rate sensitivity index m, energy dissipation factor η and material rheological instability parameter ξ of the alloy ingot under different thermal deformation parameters are calculated according to the following formula:

[0014]

[0015]

[0016]

[0017] Among them, G is the dissipation, J is the dissipation covariance, is the strain rate (s -1 ), σ is the flow stress (MPa).

[0018] In another aspect of the present application, the present application proposes a method for preparing NiTiHf alloy for aviation bearings. The method comprises: using Ni, Ti and Hf raw materials, smelting according to different predetermined chemical measurements to obtain multiple alloy ingots; performing performance tests on multiple alloy ingots to obtain performance data of the multiple alloy ingots, the performance data including at least one of hardness modulus, compressive strength, nanoindentation hardness, nanoindentation modulus, and ultimate compressive strength; obtaining the thermal processing diagram of the multiple alloy ingots according to the aforementioned method; among the multiple alloy ingots having a hot processing window in the thermal processing diagram, selecting the chemical measurement corresponding to the alloy ingot according to the performance data; determining the hot processing process parameters according to the hot processing diagram corresponding to the chemical measurement, and obtaining the NiTiHf alloy for aviation bearings by hot processing. In this way, a NiTiHf alloy with good mechanical properties can be easily obtained.

[0019] According to an embodiment of the present application, the performance test includes an XRD test, a nanoindentation test, and a room temperature compression test.

[0020] According to an embodiment of the present application, the purity of the Ni, Ti and Hf raw materials is not less than 99.9%.

[0021] In another aspect of the present application, the present application proposes a NiTiHf alloy for aviation bearings, wherein the NiTiHf alloy for aviation bearings is prepared based on the above-mentioned method. The alloy has good mechanical properties and is suitable for aviation bearings.

[0022] The above summary is for the purpose of description only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments and features described above, further aspects, embodiments and features of the present application will be readily apparent through the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The XRD spectra of the alloys in the examples and comparative examples of the present application are shown.

[0024] Figure 2 The scanning electron microscope images of the alloys prepared in the examples and comparative examples of the present application are shown.

[0025] Figure 3The EBSD analysis results of the alloys prepared in the examples and comparative examples of the present application are shown.

[0026] Figure 4 The nanoindentation test analysis results of the alloys prepared in the examples and comparative examples of the present application are shown.

[0027] Figure 5 The room temperature compression analysis results of the alloys prepared in the examples and comparative examples of the present application are shown.

[0028] Figure 6 The high temperature compression true stress-strain curves of the alloys prepared in the examples and comparative examples of the present application are shown.

[0029] Figure 7 The thermal processing diagrams of the alloys prepared in the examples and comparative examples of the present application are shown. DETAILED DESCRIPTION

[0030] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present application, and different embodiments may be combined arbitrarily without conflict. Therefore, the following description is considered to be exemplary and non-restrictive in nature.

[0031] As a first aspect of the present application, the present application proposes a method for determining hot working parameters of NiTiHf alloy for aviation bearings.

[0032] As mentioned above, adding Hf elements can improve the elastic modulus and mechanical properties of NiTi alloys. However, the addition of Hf elements leads to a decrease in the ductility of NiTiHf alloys, making it more difficult to meet the complex processing and forming processes of bearings, that is, the hot working properties of NiTiHf alloys are poor and it is difficult to meet the process requirements required for aviation bearings. Therefore, if the hot working parameters of NiTiHf alloys suitable for specific stoichiometric ratios can be easily determined, the above problems can be alleviated or even solved to a large extent.

[0033] Based on the above problems, the method proposed in the present application first adopts Ni, Ti and Hf raw materials, and melts to obtain an alloy ingot containing NiTiHf according to a predetermined stoichiometric ratio. Subsequently, by performing a hot compression test on the alloy ingot, stress-strain data is obtained, and then a thermal processing diagram of a specific stoichiometric ratio is obtained. From the thermal processing diagram, the machinable area suitable for the specific stoichiometric ratio can be determined relatively easily, so as to obtain the optimal processing parameters. Thus, the hot processing parameters of the NiTiHf alloy can be determined simply and systematically. And this method can be applicable to a variety of different NiTiHf stoichiometric ratios, which is conducive to determining the hot processing parameters of a specific alloy system according to different alloy mechanical property requirements, and therefore has good universality.

[0034] Specifically, in the method, an alloy ingot can be prepared first. For example, high-purity Ni, Ti and Hf particles with a purity of 99.9% or more can be used as raw materials, and a NiTiHf alloy ingot can be obtained by smelting in a vacuum suspension furnace. The specific size of the alloy ingot is not particularly limited. In order to meet the needs of subsequent tests, the mass of the alloy ingot obtained in this step can be 10 kg.

[0035] Subsequently, a hot compression test can be performed on the alloy ingot to obtain stress-strain data. Specifically, the stress-strain data includes the energy dissipation factor η and the material rheological instability parameter ξ of the alloy ingot under different hot deformation parameters.

[0036] Specifically, the alloy ingot can be cut to obtain multiple samples. The multiple samples are subjected to hot compression tests respectively, and the hot deformation parameters of the hot compression tests of different samples are different. The hot deformation parameters may include deformation temperature and strain rate, wherein the deformation temperature is 800-1000°C and the strain rate is 0.001-1s -1 Thus, stress-strain curves under multiple thermal deformation conditions can be obtained.

[0037] In some embodiments, the alloy ingot can be heated to a predetermined deformation temperature at a rate of 10K / s and maintained for 5 minutes, and the compression is stopped when the true strain is 0.9, and then the alloy ingot is rapidly water-cooled. The hot compression experiment is carried out in a vacuum state, and graphite lubrication can be used to reduce the friction between the alloy ingot and the clamping end.

[0038] Subsequently, multiple stress-strain curves can be analyzed based on the dynamic model of the material to calculate the energy dissipation factor η and the material rheological instability parameter ξ under different thermal deformation parameters. Specifically, the strain rate sensitivity index m can be calculated according to the following formula, and based on the strain rate sensitivity index m, the energy dissipation factor η and the material rheological instability parameter ξ can be calculated:

[0039]

[0040]

[0041]

[0042] Among them, G is the dissipation, J is the dissipation covariance, is the strain rate (s -1 ), σ is the flow stress (MPa).

[0043] Subsequently, the energy dissipation diagram of the alloy ingot can be obtained according to the relationship between the energy dissipation factor η and the temperature and strain rate. The rheological instability diagram of the alloy ingot can be obtained according to the relationship between the material rheological instability parameter ξ and the temperature and strain rate. The thermal processing diagram of the alloy ingot can be obtained by superimposing the two.

[0044] After obtaining the thermal processing diagram of the alloy ingot, the thermal processing window of the stoichiometric alloy ingot can be determined according to the thermal processing diagram, and the thermal processing temperature and strain rate can be determined, and then the specific process parameters for hot processing the stoichiometric alloy can be determined.

[0045] In another aspect of the present application, the present application proposes a method for preparing a NiTiHf alloy for aviation bearings. The method includes preparing a plurality of alloy ingots with different stoichiometric ratios, and performing performance tests on the alloy ingots with different stoichiometric ratios and determining the hot working process parameters. Subsequently, an alloy ingot with better performance can be selected from a plurality of alloy ingots with a processable window, and its hot working process parameters can be determined. Specifically, the method may include the following steps:

[0046] First, Ni, Ti and Hf raw materials are used to smelt and obtain multiple alloy ingots according to different predetermined chemical quantities. The method of smelting and obtaining multiple alloy ingots can be the same as the operation of obtaining alloy ingots in the method described above, which will not be repeated here.

[0047] Subsequently, a plurality of the alloy ingots may be subjected to performance tests to obtain performance data of the plurality of alloy ingots. The performance data includes at least one of hardness modulus, compressive strength, nanoindentation hardness, nanoindentation modulus, and ultimate compressive strength. Performance tests include XRD tests, nanoindentation tests, and room temperature compression tests. For example, the proportion of each phase in the alloy may be analyzed according to the XRD test, and the nanoindentation hardness and elastic modulus of the alloy may be obtained according to the nanoindentation test, such as specifically, according to the nanoindentation hardness and modulus test. According to the room temperature compression test, a compression curve is obtained to obtain the ultimate compressive strength and ultimate compression strain data of the alloy ingot.

[0048] Subsequently, the thermal processing diagrams of the plurality of alloy ingots can be obtained according to the method described above. The alloy ingots with a thermal processing window in the plurality of thermal processing diagrams are selected, and the alloy ingots with better performance data are selected with reference to the performance test data obtained previously, so that the corresponding stoichiometry thereof is determined as the stoichiometric ratio of the alloy to be prepared. Subsequently, the thermal processing process parameters are determined according to the thermal processing diagram of the stoichiometric ratio.

[0049] Thus, the stoichiometric ratio and hot working parameters have been obtained, and the NiTiHf alloy with good mechanical properties can be easily obtained.

[0050] In another aspect of the present application, the present application proposes a NiTiHf alloy for aviation bearings, wherein the NiTiHf alloy for aviation bearings is prepared based on the method described above. The alloy has good mechanical properties, is suitable for aviation bearings, and has the potential to become a new generation of aviation bearing materials.

[0051] Since the alloy is obtained by the aforementioned method, the alloy has all the characteristics and advantages of the alloy obtained by the aforementioned method, which will not be described in detail here. In general, the NiTiHf alloy hot working diagram drawn according to the above method can obtain the instability area and suitable processing area of ​​the alloy, so that the hot working process parameters of the NiTiHf alloy for aviation bearings with high elastic modulus and hot working deformation can be easily determined.

[0052] Therefore, the method proposed in this application can provide a new NiTiHf alloy with an ideal processing window for a new generation of aviation bearing materials, which has the advantages of high elastic modulus, hardness, ultra-high temperature resistance, low density and corrosion resistance. The process is simple, can significantly improve the service performance and life of aviation bearings, and can be widely used.

[0053] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.

[0054] The method proposed in this application is described below by means of specific examples. The methods used in the following examples are conventional methods unless otherwise specified, and the reagents used are commercially available reagents unless otherwise specified.

[0055] Example 1

[0056] High-purity Ni, Ti and Hf of 99.9% or above were selected as raw materials, and a vacuum suspension furnace was used for smelting to obtain a 10 kg 56Ni36Ti8Hf (wt.%) alloy ingot.

[0057] Cylindrical specimens with sizes of Φ4×6mm and Φ8×12mm were cut from the center of the above ingots using a CNC wire cutting machine.

[0058] XRD, SEM and EBSD were used to test the microstructure of 56Ni36Ti8Hf alloy. The test results are as follows: Figure 1 (the horizontal axis is 2θ angle), Figure 2 Medium b and Figure 3 As shown in b, the 56Ni36Ti8Hf alloy is mainly composed of matrix NiTi phase and Ni3Ti2 phase, with an average grain size of 82.5μm.

[0059] The nanoindentation hardness and elastic modulus of 56Ni36Ti8Hf alloy were tested by nanoindentation instrument, and the nanoindentation hardness and elastic modulus of the alloy were 4.84 and 80.33 GPa respectively. Figure 4 As shown ( Figure 4 In the sample, displacement refers to displacement, load refers to load, category refers to sample category, hardness refers to hardness, and modulus refers to modulus).

[0060] A universal testing machine was used to perform room temperature compression tests on Φ4×6 mm 56Ni36Ti8Hf alloy samples at a compression strain rate of 1.38×10 -4 s -1 Until the sample breaks, the compression curve is as follows Figure 5 As shown ( Figure 5 stress-stress, strain-strain, Hf element content-Hf element content, ultimate compressive strain-ultimate compressive strain). The ultimate compressive strength and ultimate compressive strain of 56Ni36Ti8Hf alloy are 2464.6MPa and 0.268 respectively.

[0061] A series of hot compression orthogonal tests were carried out on Φ8×12 mm 56Ni36Ti8Hf alloy samples using a thermal simulation test machine at temperatures of 800, 850, 900, 950 and 1000 °C and strain rates of 0.001, 0.01, 0.1 and 1 s -1 , the true strain is 0.9, and quenching is performed after compression. Based on the dynamic material model, the stress-strain data when the strain is 0.9 is selected, such as Figure 6 As shown ( Figure 6 The strain rate sensitivity index, energy dissipation factor and material rheological instability parameter of 56Ni36Ti8Hf alloy were calculated.

[0062] The energy dissipation diagram and instability diagram of 56Ni36Ti8Hf alloy are drawn, and the thermal processing diagram of the alloy is obtained by superimposing the two, such as Figure 7 As shown in b ( Figure 7 In the figure, the shaded area is the unstable area, the green frame line is the suitable processing area, and the contour line is the distribution of energy dissipation.

[0063] It is further concluded that the 56Ni36Ti8Hf alloy is unstable under low temperature and high strain rate conditions, and the instability zone is concentrated in the low temperature and high strain rate area. The processing area has a high energy dissipation rate, concentrated at 850-950℃, 0.003-0.032s -1 The optimal processing parameters of 56Ni36Ti8Hf alloy are 900℃, 0.01s -1 .

[0064] Example 2

[0065] Firstly, high-purity Ni, Ti and Hf of 99.9% or above are selected as raw materials, and a vacuum suspension furnace is used for smelting to obtain a 10 kg 56Ni32Ti12Hf (wt.%) alloy ingot.

[0066] Cylindrical specimens with sizes of Φ4×6mm and Φ8×12mm were cut from the center of the above ingots using a CNC wire cutting machine.

[0067] XRD, SEM and EBSD were used to detect the microstructure of 56Ni32Ti12Hf alloy. Figure 1 , Figure 2 c and Figure 3 As shown in c. 56Ni32Ti12Hf alloy is mainly composed of matrix Ni3Ti phase and Ni3Ti2 phase, with an average grain size of 82.3μm.

[0068] The nanoindentation hardness and elastic modulus of 56Ni32Ti12Hf alloy were tested by nanoindentation instrument, and the nanoindentation hardness and elastic modulus of the alloy were 5.47 and 83.11 GPa respectively. Figure 4 shown.

[0069] A universal testing machine was used to perform room temperature compression tests on Φ4×6 mm 56Ni32Ti12Hf alloy samples at a compression strain rate of 1.38×10 -4 s -1 Until the sample breaks, the compression curve is as follows Figure 5 The ultimate compressive strength and ultimate compressive strain of 56Ni32Ti12Hf alloy are 2606.4MPa and 0.265 respectively.

[0070] A series of hot compression orthogonal tests were carried out on Φ8×12 mm 56Ni32Ti12Hf alloy samples using a thermal simulation test machine at temperatures of 800, 850, 900, 950 and 1000 °C and strain rates of 0.001, 0.01, 0.1 and 1 s -1 , the true strain is 0.9, and quenching is performed after compression. Based on the dynamic material model, the stress-strain data when the strain is 0.9 is selected, such as Figure 6 The strain rate sensitivity index, energy dissipation factor and material rheological instability parameter of 56Ni32Ti12Hf alloy are calculated.

[0071] The energy dissipation diagram and instability diagram of 56Ni32Ti12Hf alloy are drawn, and the two are superimposed to obtain the thermal processing diagram, such as Figure 7 As shown in c in the figure. The shaded area in the figure is the unstable area, the green frame line is the suitable processing area, and the contour line is the distribution of energy dissipation. It can be concluded that 56Ni32Ti12Hf alloy is unstable under low temperature and high strain rate conditions, and the unstable area is concentrated in the high strain rate area. The area suitable for processing has a higher energy dissipation rate, concentrated at 875-975℃, 0.003-0.032s -1 The optimal processing parameters of 56Ni32Ti12Hf alloy are 900℃, 0.01s -1 .

[0072] Comparative Example 1

[0073] High-purity Ni and Ti of 99.9% or above are selected as raw materials; a vacuum suspension furnace is used for smelting to obtain a 10 kg 56Ni44Ti (wt.%) alloy ingot.

[0074] Cylindrical specimens with sizes of Φ4×6mm and Φ8×12mm were cut from the center of the above ingots using a CNC wire cutting machine.

[0075] XRD, SEM and EBSD were used to detect the microstructure of 56Ni44Ti alloy. Figure 1 , Figure 2 a and Figure 3 As shown in a. The 56Ni44Ti alloy is mainly composed of the matrix NiTi phase, and the average grain size is 86.3μm.

[0076] The nanoindentation hardness and elastic modulus of the 56Ni44Ti alloy were tested by a nanoindenter and the nanoindentation hardness and elastic modulus of the alloy were 3.36 and 67.70 GPa, respectively. Figure 4 shown.

[0077] A universal testing machine was used to perform room temperature compression tests on Φ4×6 mm 56Ni44Ti alloy samples at a compression strain rate of 1.38×10 -4 s -1 Until the sample breaks, the compression curve is as follows Figure 5 The ultimate compressive strength and ultimate compressive strain of 56Ni44Ti alloy are 2152.5MPa and 0.382 respectively.

[0078] A series of hot compression orthogonal tests were carried out on Φ8×12 mm 56Ni44Ti alloy samples using a thermal simulation test machine at temperatures of 800, 850, 900, 950 and 1000 °C and strain rates of 0.001, 0.01, 0.1 and 1 s -1 , the true strain is 0.9, and quenching is performed after compression.

[0079] Based on the dynamic material model, the stress-strain data when the strain is 0.9 is selected, such as Figure 6 The strain rate sensitivity index, energy dissipation factor and material rheological instability parameter of 56Ni44Ti alloy are calculated.

[0080] The energy dissipation diagram and instability diagram of 56Ni44Ti alloy are drawn, and the two are superimposed to obtain the thermal processing diagram, such as Figure 7 The shaded area in the figure is the unstable area, the green frame line is the suitable processing area, and the contour line is the distribution of energy dissipation.

[0081] 56Ni44Ti alloy is unstable under low temperature and high strain rate conditions, and the unstable zone is concentrated in the high strain rate area. The processing area has a high energy dissipation rate, concentrated at 825-925℃, 0.001-0.032s -1 The optimal processing parameters of 56Ni44Ti alloy are 850℃, 0.01s -1 .

[0082] By comparing Example 1, Example 2 and Comparative Example 1, it is found that the elastic modulus and hardness of the NiTi alloy are improved to a certain extent after the addition of the Hf element, and the alloy has the property of being hot-processable. Figure 1 The XRD analysis patterns of the embodiment and the comparative example show that Ni3Ti2 strengthening phase appears in both 56Ni32Ti8Hf and 56Ni32Ti12Hf alloys. Figure 2 and Figure 3 It is found that the size and quantity of Ni3Ti2 strengthening phase in the alloy increase with the increase of Hf element content. Figure 4 and Figure 5The nanoindentation and room temperature compression test analysis of the embodiments and comparative examples show that the addition of Hf element significantly improves the hardness modulus and compressive strength of the alloy. This is mainly due to the load transfer strengthening effect of the Ni3Ti2 strengthening phase, which improves the mechanical properties of the alloy. The nanoindentation hardness of 56Ni44Ti, 56Ni32Ti8Hf and 56Ni32Ti12Hf alloys are 3.36, 4.84 and 5.47 GPa respectively, the modulus is 67.70, 80.33 and 83.11 GPa respectively, and the ultimate compressive strength is 2152.5, 2464.6 and 2606.4 MPa respectively. Figure 6 The hot compression stress-strain curves of the examples and comparative examples show that the flow stress of the alloy is significantly increased with the addition of Hf element. Figure 7 The hot working diagrams of the embodiment and the comparative example show that the addition of Hf element reduces the hot working window of the alloy, but there are optimal hot working process parameters. The hot working process of the present invention can provide an operating guide for determining the subsequent forging process.

[0083] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0084] In the present disclosure, unless otherwise clearly specified and limited, a first feature being “above” or “below” a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being “above”, “above”, and “above” a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is lower in level than the second feature.

[0085] The disclosure above provides many different embodiments or examples to implement different structures of the present disclosure. In order to simplify the present disclosure, the components and settings of specific examples are described above. Of course, they are only examples, and the purpose is not to limit the present disclosure. In addition, the present disclosure can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplification and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed.

[0086] The above are only specific embodiments of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any technician familiar with the technical field can easily think of various changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

[0087] The above application provides many different embodiments or examples to realize the different structures of the present application. In order to simplify the present application, the parts and settings of specific examples are described above. Of course, they are only examples, and the purpose is not to limit the present application. In addition, the present application can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplification and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed.

[0088] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for determining hot working parameters of NiTiHf alloy for aviation bearings, characterized in that: include: Using Ni, Ti and Hf raw materials, and melting according to the stoichiometric amount of the NiTiHf alloy to obtain an alloy ingot; Performing a hot compression test on the alloy ingot to obtain stress-strain data of the alloy ingot, wherein the stress-strain data includes an energy dissipation factor η and a material rheological instability parameter ξ of the alloy ingot under different thermal deformation parameters; An energy dissipation diagram is obtained according to the relationship between the energy dissipation factor η and the temperature and strain rate, and a rheological instability diagram is obtained according to the relationship between the material rheological instability parameter ξ and the temperature and strain rate; According to the energy dissipation diagram and the rheological instability diagram, a thermal processing diagram of the alloy ingot is obtained by superposition, and the thermal processing process parameters of the alloy ingot are determined. The thermal processing parameters include thermal processing temperature and strain rate.

2. The method according to claim 1, characterized in that In the thermal compression test, the thermal deformation parameters include deformation temperature and strain rate. The deformation temperature is 800-1000°C and the strain rate is 0.001-1s -1 .

3. The method according to claim 2, characterized in that The thermal compression test includes: The alloy ingot was heated to a predetermined deformation temperature at a rate of 10 K / s and maintained for 5 minutes. When the true strain was 0.9, compression was stopped and then water-cooled.

4. The method according to claim 3, characterized in that The hot compression experiment was carried out in a vacuum state, and graphite lubrication was used to reduce the friction between the alloy ingot and the clamping end.

5. The method according to claim 4, characterized in that Obtaining the energy dissipation factor η and the material rheological instability parameter ξ includes: The stress-strain curve of the alloy ingot under multiple thermal deformation parameters is obtained, the strain rate sensitivity index m is obtained, and based on the strain rate sensitivity index m, the energy dissipation factor η and the material rheological instability parameter ξ are calculated.

6. The method according to claim 5, characterized in that The strain rate sensitivity index m, energy dissipation factor η and material rheological instability parameter ξ of the alloy ingot under different thermal deformation parameters are calculated according to the following formula: Among them, G is the dissipation, J is the dissipation covariance, is the strain rate (s -1 ), σ is the flow stress (MPa).

7. A method for preparing NiTiHf alloy for aviation bearings, characterized in that: include: Using Ni, Ti and Hf raw materials, smelting according to different predetermined chemical quantities to obtain multiple alloy ingots; Performing performance tests on a plurality of the alloy ingots to obtain performance data of the plurality of alloy ingots, wherein the performance data includes at least one of hardness modulus, compressive strength, nanoindentation hardness, nanoindentation modulus, and ultimate compressive strength; According to the method according to any one of claims 1 to 6, obtaining thermal processing maps of the plurality of alloy ingots; Among the plurality of alloy ingots having a hot working window in the hot working map, selecting a stoichiometry corresponding to the alloy ingot according to the performance data; The hot working process parameters are determined according to the hot working diagram corresponding to the chemical measurement, and the NiTiHf alloy for aviation bearings is obtained by hot working.

8. The method according to claim 7, characterized in that The performance tests include XRD test, nanoindentation test and room temperature compression test.

9. The method according to claim 7 or 8, characterized in that: The purity of the Ni, Ti and Hf raw materials is not less than 99.9%.

10. A NiTiHf alloy for aviation bearings, characterized in that: The NiTiHf alloy for aviation bearings is prepared based on the method described in any one of claims 7-9.

Citation Information

Patent Citations

  • Method for automatically drafting material hot working chart

    CN101201307A

  • Formulating method of high-temperature alloy GH984G18 hot working technology

    CN106929783A

  • Making method of nickel-based alloy hot working process

    CN110964994A

  • Integrated Shape / Property Control Method for Hot Power Spinning of a Cylindrical Part Based on Hot Processing Map

    US20210276067A1